2015
DOI: 10.1111/febs.13565
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteriophage D29 holin C‐terminal region functionally assists in holin aggregation and bacterial cell death

Abstract: Holins are phage-encoded small transmembrane proteins that perforate the bacterial cytoplasmic membrane. In most cases, this process allows the phage-encoded peptidoglycan hydrolases to act on the cell wall, resulting in host cell lysis and phage release. We report a detailed functional characterization of Mycobacterium phage D29 gp11 coding for a putative holin that, upon expression, rapidly kills both Escherichia coli and Mycobacterium smegmatis. We dissected Gp11 by making several deletions and expressing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 60 publications
10
53
0
Order By: Relevance
“…Similar increase in fluorescence is not observed when an inactive holin mutant, HolG28D, is expressed (Fig. 2); we have previously shown that HolG28D is incapable of causing bacterial cell death (Kamilla and Jain, 2016). These studies thus confirm that the sytox green assay can be used to examine the properties of membrane pore forming proteins.…”
Section: Sytox Green Assay To Compare D29 Mycobacteriophage Holin Andsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar increase in fluorescence is not observed when an inactive holin mutant, HolG28D, is expressed (Fig. 2); we have previously shown that HolG28D is incapable of causing bacterial cell death (Kamilla and Jain, 2016). These studies thus confirm that the sytox green assay can be used to examine the properties of membrane pore forming proteins.…”
Section: Sytox Green Assay To Compare D29 Mycobacteriophage Holin Andsupporting
confidence: 79%
“…The expression of D29 mycobacteriophage holin and its mutant was achieved as described previously (Kamilla and Jain, 2016). Briefly, E. coli BL21(DE3) cells carrying expression plasmids were grown at 37°C in LB-broth supplemented with 100 µg ml -1 ampicillin.…”
Section: Real-time Monitoring Of the Expression Of D29 Mycobacteriophmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been proposed that the C-terminal cytosolic domain of holin forms a coiledcoil motif that promotes holin-mediated bacterial cytotoxicity through oligomerization. 51 Hence, it is likely that the second transmembrane domain facilitates the functioning of the other domains of holin: (i) conformational switch of the first transmembrane domain, and (ii) oligomerization of the C-terminal domain. Through this study, we find that the second transmembrane domain of Mycobacteriophage D29 holin can adopt multiple conformations (a-helical and PPII-like forms) in solution.…”
Section: Discussionmentioning
confidence: 99%
“…TM2 does not possess the conserved GX 2/3 G motif required for helix dimerization, 54,55 nor does it show any propensity for a coiled-coil motif. 51 Hence, it is unclear whether TM2 can form homo-or hetero-oligomers in vivo. We do find that TM2 has a short hydrophobic segment (Supporting Information Figure S8), which might facilitate TM2 localization in the membrane.…”
mentioning
confidence: 99%